Calculation of alpha particles detection efficiency for polycarbonate detector using Geant4 toolkit - A. Moslehi; S. Baradaran; M. Taheri (Journal of Nuclear Research and Applications, 2022)
In the present work, alpha particles detection efficiency of polycarbonate detector (PC) is calculated using Geant4 simulation toolkit. A PC detector with 250 µm thickness and dimension of 2.5 × 2.5 cm2 is considered. Assuming the passage of alpha particles of an 241Am source through brass collimators with different lengths, various alpha energies ranging from 0.2 to 2.5 MeV are modeled. Also, an etching layer of 6 µm related to a given electrochemical etching process as well as a threshold stopping power of 240 keV µm-1 required for forming the tracks are used as the input data. The detection efficiency is determined as the ratio of registered tracks per unit area to the number of alpha particles reaching the PC detector surface. To validate the simulation, the results are compared with the experimental data reported in the literature. It is found that the both results agree well within a maximum variation of 10%.